Hydriding of titanium: Recent trends and perspectives in advanced characterization and multiscale modeling. Issue 6 (December 2022) - Zhu, Yakun; Wook Heo, Tae; Rodriguez, Jennifer N.; Weber, Peter K.; Shi, Rongpei; Baer, Bruce J.; Morgado, Felipe F.; Antonov, Stoichko; Kweon, Kyoung E.; Watkins, Erik B.; Savage, Daniel J.; Chapman, James E.; et al.
Graphical abstract: Highlights: This perspective article introduces the key unanswered questions and challenges in understanding hydride formation in Ti alloys. We propose new perspectives on how to solve these remaining issues by integrating advanced characterization and multiscale modeling. The paper draws upon our own work, as well as provide a contextual review of existing literature studies focused on the integration of novel experimental and computational tools for detailed mechanistic understanding. The field of degradation science is changing rapidly, and this paper will provide specific examples of how new tools can be applied to an old problem. Abstract: Titanium (Ti) and its alloys are attractive for a wide variety of structural and functional applications owing to excellent specific strength, toughness and stiffness, and corrosion resistance. However, if exposed to hydrogen sources, these alloys are susceptible to hydride formation in the form of TiHx (0 < x ≤ 2), leading to crack initiation and mechanical failure due to lattice deformation and stress accumulation. The kinetics of the hydriding process depends on several factors, including the critical saturation threshold for hydrogen within Ti, the specific interaction of hydrogen with protective surface oxide, the rates of mass transport, and the kinetics of nucleation and phase transformation. Unfortunately, key knowledge gaps and challenges remain regarding the details of these coupled processes, which take place across vast ranges of time and length scales and are often difficult to probe directly. This work reviews recent advances in multiscale characterization and modeling efforts in Ti hydriding. We identify unanswered questions and key challenges, propose new perspectives on how to solve these remaining issues, and close knowledge gaps by discussing and demonstrating specific opportunities for integrating advanced characterization and multiscale modeling to elucidate chemistry and composition, microstructure phenomena, and macroscale performance and testing.